Dendritic cell metabolism: moving beyond in vitro-culture-generated paradigms. (April 2021) - Minarrieta, Lucía; Velasquez, Lis Noelia; Sparwasser, Tim; Berod, Luciana
Graphical abstract: Highlights: Knowledge on DC metabolism is based on in vitro bulk-cultures. Current methods use metabolic inhibitors or measure metabolic enzymes/metabolites. Most in vitro models correlate poorly with bona fide dendritic cells. Progress is possible with single-cell level techniques plus transgenic mouse models. Abstract : Dendritic cells (DCs) are key orchestrators of immunity and tolerance. It has become evident that DC function can be influenced by cellular metabolic programs. However, conclusions from early metabolic studies using in vitro GM-CSF DC cultures fail to correlate with bona fide DC populations. Here, we discuss the existing paradigms in the DC metabolism field, focusing on the limitations of the models utilized. Furthermore, we introduce alternative models to generate DCs in vitro that better emulate DCs found in vivo. Finally, we highlight new techniques to evaluate DC metabolism at the single-cell level. The combination of these two strategies could help advance the DC metabolism field towards a more physiological understanding, which is crucial for the development of effective DC-based therapies.